JMY Functions as Actin Nucleation-Promoting Factor and Mediator for p53-Mediated DNA Damage in Porcine Oocytes - Lin, Zili (Public Library of Science, 2014)
Junction-mediating and regulatory protein(JMY) is a multifunctional protein with roles in the transcriptional co-activation of p53 and the regulation of actin nucleation promoting factors and, hence, cell migration; however, its role in the maturation of porcine oocytes is unclear. In the current study, we investigated functional roles of JMY in porcine oocytes. Porcine oocytes expressed JMY mRNA and protein, and the mRNA expression level decreased during oocyte maturation. Knockdown of JMY by RNA interference decreased the rate of polar body extrusion, validating its role in the asymmetric division of porcine oocytes. JMY knockdown also down-regulated the mRNA and protein levels of actin and Arp2/3. Furthermore, JMY accumulated in the nucleus in response to DNA damage, and JMY knockdown suppressed DNA damage-mediated p53 activation. In conclusion, our results show that JMY has important roles in oocyte maturation as a regulator of actin nucleation-promoting factors and an activator of p53 during DNA damage during DNA damages in porcine oocytes.